Uso do solo e Dinâmica dos Nutrientes nas Águas do Reservatório da Hidrelétrica de Manso no Estado de Mato Grosso, Brasil Central - Jeater Waldemar Maciel Correa Santos; Simoni Maria Loverde Oliveira; William Pietro de Souza (Confins)
This survey had as to aim to comprehend the influence use and occupation of land in the area where that formed the Manso Reservoir - Chapada dos Guimarães-MT/Brasil - about the variation of nutrients in their waters in the phases of filling (dez/1999 to December 2000) and stabilization (dec/2001 the dec/2002). So was used geoprocessing resources for image classification and production of maps for use and occupation of land, statistical analyzes were also performed to assess the variance time-spatial limnological data collected in situ and also the level of correlation of these data with the spectral nature. As a result it was found that in only 7 months the water lamina of reservoir had already covered more than 60% of the previewed area for filling leaving submerged almost the all original vegetation existing in the area, it was 62%covered with forests and savannas and 19% of grasses for grazing cattle. The decomposition of this organic biomass flooded has provided nutrients to the water, and has influenced in the time-spatial variation of concentrations of total nitrogen (NT) and total phosphorus (PT), especially during filling phase of the reservoir, where its contribution may have been more important than that resulting from the export of nitrogen and phosphorus for their sub-basins of contribution. There was also a positive correlation between total biomass flooded by the reservoir lake in the time-spatial distribution and concentrations of total nitrogen, and the local weather rhythm has affected the behavior of the concentrations of these nutrients, especially in the case of total phosphorus. Thus, it was concluded that the methodology used it is efficient for the purposes of the study, since it allowed understand how the use and occupation of soil the area flooded by the reservoir of Manso influenced the time-spatial variation of water quality in the analyzed period.